Properties of Ni-TiO₂ composites electrodeposited from methanesulfonate electrolyte - Sknar, Yu.E.; Savchuk, O.O.; Sknar, I.V.; Danilov, F.I. (Functional Materials, 2017)
The effect of conditions of preliminary preparation of methanesulfonate suspension electrolyte used in electrodeposition of Ni-TiO₂ composites, on the aggregate stability of the dispersed phase is studied. It has been found that increase in the electrolyte exposition time prior to the dispersion analysis allows obtaining the equilibrium sizes of TiO₂ particles, whose radius is close to 1 µm. It is shown that composition of the composites varies with the coating thickness and reaches the constant value at thicknesses above 6 µm. The titanium dioxide content of the composite coatings increases with increasing the concentration of TiO₂ in the suspension and decreasing the current density. Introduction of the dispersed phase into nickel matrix enhances the internal stresses and microhardness of the deposits, which is related with structural changes in the nickel matrix. X-ray studies shows that crystallite size of the composite is slightly less than that of pure nickel. A small refinement of the composite matrix grains and presence of the dispersed phase of TiO₂ on their surface are recorded while. It has been revealed that photocatalytic activity of the coatings correlates with the titanium dioxide content of the deposits.